Intersections of Nationhood in the Plays of Robert Yeo: A Study of “One Year Back Home and Changi” - Sankaran, Chitra (2014)
Ninth Biennial Symposium on Literatures and Cultures of the Asia-Pacific Region, 8-11 December, 1999, National University of Singapore, Singapore